Identification of propentofylline metabolites in rats by gas chromatography/mass spectrometry - Kwon, OS; Ryu, JC (PHARMACEUTICAL SOCIETY KOREA, 2000)
Propentofylline (PPF, 3-methyl-1-(5-oxohexyl)-7-propylxanthine) has been reported to be a compound for treatment of both vascular dementia and dementia of the Alzheimer type. The short half-life (about 15 min) of PPF at the terminal elimination phase and poor bioavailability after oral administration of PPF to rabbits (Kim et al., 1992) suggest in part that this drug takes the extensive first-pass metabolism in the liver. in addition, the metabolic pathway for PPF remains unclear. The objective of this experiment is to identify urinary metabolites of PPF in rats. For the identification of the metabolites, rat urine was collected after oral administration of 100 mg/kg PPF. PPF metabolite, 3-methyl-1-(5-hydroxyhexyl)-7-propylxanthine, was synthesized and confirmed by gas chromatography/mass spectroscopy (GC/MS) and H-1 nuclear magnetic resonance spectroscopy. The urinary metabolites of PPF were extracted with diethyl ether and identified by electron impact and chemical ionization GC/MS. One urinary metabolite was confirmed to be 3-methyl-1-(5-hydroxyhexyl)-7-propylxanthine by synthesized authentic compound. Several metabolites of monohydroxy- and dihydroxy-PPF were identified based on mass fragmentation of both intact and trimethylsilylated derivatives of PPF metabolites and the novel structure of these metabolites is suggested based on mass spectra.